2017
DOI: 10.22330/heb/323/085-108
|View full text |Cite
|
Sign up to set email alerts
|

Youth Injuries as a Function of Sex, Life History, and Neighborhood Safety

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…As predicted, residents of higher quality neighborhoods exhibited a slower LH strategy. Further support for the association between neighborhood environment and LH strategy was recently found by Johnsen et al (2017) who found that neighborhood safety was associated with both psychometric (mini-K score) and biometric (age of first sex) indices of LH strategy. Though tentative, what these studies suggest is that varying ecological conditions may exert their influence on developmental outcomes (personality traits, behavior, etc.)…”
Section: Sources Of Variance In Lh Strategymentioning
confidence: 69%
“…As predicted, residents of higher quality neighborhoods exhibited a slower LH strategy. Further support for the association between neighborhood environment and LH strategy was recently found by Johnsen et al (2017) who found that neighborhood safety was associated with both psychometric (mini-K score) and biometric (age of first sex) indices of LH strategy. Though tentative, what these studies suggest is that varying ecological conditions may exert their influence on developmental outcomes (personality traits, behavior, etc.)…”
Section: Sources Of Variance In Lh Strategymentioning
confidence: 69%
“…For instance, Barash (2016) makes a strong case for human mating systems, across time and place, as shaped by such important evolutionarily relevant factors such as sex differences in required parental investment. Similarly, Johnsen, Kruger, Geher, Wiegand, Shaiber, and Garcia (2017) provide evidence that such factors as risk-taking, proneness toward physical injuries, mating strategies, and life history strategy map strongly onto male/female differences in humans. When it comes to understanding why men and women behave differently from one another in the mating domain, the evolutionary perspective has been of great heuristic value.…”
Section: Evolutionary Psychology and Sex Differencesmentioning
confidence: 89%
“…Male mortality rates have been shown to vary enormously when compared with female mortality rates (Kraemer, 2000). This fact seems to relate to the well-documented finding regarding differential rates of death and injury across the sexes (see Kruger & Nesse, 2006;Johnsen et al, 2017) with males across the life cycle being more likely to die or get injured compared with females. This tendency is exacerbated during adolescence and young adulthood, suggesting that it may be rooted in relatively risky courtship strategies that males employ as part of mate-acquisition processes.…”
Section: Evosmentioning
confidence: 95%
“…One component of pursuing short-term mating scenarios and sexual variety is risk-taking. While it is the case that both sexes incur more risk under short-term mating scenarios (Sylwester and Pawłowski, 2011) and certain environmental factors (i.e., alcohol consumption) can increase risk-taking in both sexes (George et al, 2008), the evidence to date shows that younger males take on a more risky life history strategy (Daly and Wilson, 1988;Kruger, 2008;Wang et al, 2009) with males willing to incur more risk than females in a variety of contexts (e.g., Byrnes et al, 1999;Courtenay, 2000;Waldron et al, 2005;George et al, 2008;Pawłowski et al, 2008;Johnson et al, 2017). Males will increase their risk-taking when in the presence of an attractive female (Ronay and von Hippel, 2010) or when presented with attractive female face stimuli (Baker and Maner, 2008).…”
Section: Introductionmentioning
confidence: 99%